2021
DOI: 10.29121/granthaalayah.v9.i6.2021.4039
|View full text |Cite
|
Sign up to set email alerts
|

The India Mutations and B.1.617 Delta Variants: Is There a Global "Strategy" for Mutations and Evolution of Variants of the Sars-Cov2 Genome?

Abstract: In this paper, we run for all INDIA mutations and variants a biomathematical numerical method for analysing mRNA nucleotides sequences based on UA/CG Fibonacci numbers proportions (Perez, 2021). In this study, we limit ourselves to the analysis of whole genomes, all coming from the mutations and variants of SARS-CoV2 sequenced in India in 2020 and 2021. We then demonstrate - both on actual genomes of patients and on variants combining the most frequent mutations to the SARS-CoV2 Wuhan genomes and then to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, this Prion regio n TOTALLY disappears from the new OMICRON 21K (SA1) and 21L (Minesota) variants. It is mathematically demonstrated that a hidden fractal order exists in DNA and RNA genomic sequences Perez (1991), , Perez (2021a), Perez (2021b) . It consists of long-range Fibonacci meta-structures that are being thought to be associated with genome overall stability in relation with their conformational structure and dynamic.…”
Section: International Journal Of Research -Granthaalayahmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this Prion regio n TOTALLY disappears from the new OMICRON 21K (SA1) and 21L (Minesota) variants. It is mathematically demonstrated that a hidden fractal order exists in DNA and RNA genomic sequences Perez (1991), , Perez (2021a), Perez (2021b) . It consists of long-range Fibonacci meta-structures that are being thought to be associated with genome overall stability in relation with their conformational structure and dynamic.…”
Section: International Journal Of Research -Granthaalayahmentioning
confidence: 99%
“…In two articles published in 2021 Perez (2021a) and Perez (2021b) , we showed how the FIBONACCI fractal analysis method makes it possible to measure the progressive adaptation of successive variant genomes to the human host. Thus, we demonstrated how at the double levels of the spike and of the whole genome, Fibonacci meta-structures in UA / CG proportions of covering the entire genome sequence were permanently reinforced between the original Wuhan strain then the 3 successive worldwide variants D614G, ALPHA, and DELTA.…”
Section: Introductionmentioning
confidence: 99%